2015
DOI: 10.1080/1065657x.2015.1013584
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Quality by Compost and Hazelnut Husk Applications in a Hazelnut Orchard

Abstract: In this study, changes in some soil quality indexes in a hazelnut orchard located in the Black Sea Region of Turkey were investigated after 6 months of compost (CMP) and hazelnut husk (HH) applications. CMP and HH applications increased soil organic carbon (OC) content from 1.40% to 2.57 and 3.51%, and electrical conductivity from 0.06 dS m ¡1 to 0.20 and 0.91 dS m ¡1 , respectively (P < 0.01). In comparison to control treatment, CMP and HH applications increased the sum of exchangeable cations by 31 and 37%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Positive effects on soil properties caused by hazelnut husks were also reported by Ozdemir et al [34] where the authors suggested that hazelnut husks could be used in composted mixes with wastewater biosolids for the production of ornamental plants. Moreover, Aşkın and Aygün [35] highlighted the beneficial impact of hazelnut husk compost on soil organic matter content and water holding capacity, while Gülser et al [36] and Gülser and Candemir [37] indicated the slow mineralization rate of hazelnut husks and the improvements they induce in soil hydraulic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Positive effects on soil properties caused by hazelnut husks were also reported by Ozdemir et al [34] where the authors suggested that hazelnut husks could be used in composted mixes with wastewater biosolids for the production of ornamental plants. Moreover, Aşkın and Aygün [35] highlighted the beneficial impact of hazelnut husk compost on soil organic matter content and water holding capacity, while Gülser et al [36] and Gülser and Candemir [37] indicated the slow mineralization rate of hazelnut husks and the improvements they induce in soil hydraulic properties.…”
Section: Resultsmentioning
confidence: 99%
“…There were also significant positive correlations among the micro nutrient contents of soils. Gülser et al (2015) found that addition of compost and organic residue into soil increased plant available nutrient contents of the soil in a hazelnut orchard and soil organic matter content showed significant positive correlations with EC, Ca, and sum of exchangeable cations. In another study, Candemir and Gülser (2011) reported that soil bulk density reduced with organic waste application and generally gave significant negative correlations with organic matter and other soil properties.…”
Section: Soil Quality Classification In Vineyard Fieldsmentioning
confidence: 91%
“…There were also significant positive correlations among DTPA extractable micro nutrient contents of soils. Gülser et al (2015) reported that compost and organic residue applications to soil in a hazelnut orchard increased plant available nutrient contents of the soil and OM content had significant positive relations with EC, exch. Ca, and sum of exch.…”
Section: Soil Quality Classification For Olive Groves Areasmentioning
confidence: 99%